2009
DOI: 10.1021/ja8088247
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine Dimerization-Based Molecular Beacons Using Near-IR Fluorescence

Abstract: Herein we demonstrate the use of a novel dimerization-based molecular beacon (MB) probe consisting of two metallo-phthalocyanine (Pc) fluorophores that use near-IR fluorescence, appropriate for highly specific and sensitive in-vivo and/or in-vitro DNA/RNA detection. Pc's possess a propensity to form non-fluorescent H-dimers that is utilized as the molecular "off" switch in the closed MB conformation. The "on" switch, which is generated when the solution target binds to the loop of the MB forming the open form,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 19 publications
0
58
0
Order By: Relevance
“…Pcs have a number of characteristic properties such as high thermal stability, unique photophysical properties, intense color, non-toxicity, and high phototoxicity upon irradiation with light, contributing to their effectiveness in different research areas. Their easily tunable photochemical and photophysical properties such as narrow absorbance and emission band and resistance to photobleaching, by changing the substitution pattern around the Pc aromatic core and/or the central metal atom, makes these compounds highly appropriate for applications such as PCR, single gene mutation detection, and resonance energy transfer-based assays (9).…”
Section: Near-ir (Nir) Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pcs have a number of characteristic properties such as high thermal stability, unique photophysical properties, intense color, non-toxicity, and high phototoxicity upon irradiation with light, contributing to their effectiveness in different research areas. Their easily tunable photochemical and photophysical properties such as narrow absorbance and emission band and resistance to photobleaching, by changing the substitution pattern around the Pc aromatic core and/or the central metal atom, makes these compounds highly appropriate for applications such as PCR, single gene mutation detection, and resonance energy transfer-based assays (9).…”
Section: Near-ir (Nir) Dyesmentioning
confidence: 99%
“…They are specifically useful fluorescence on-off systems offering high target to background ratio due to Pcs high extinction coefficients and strong and narrow emission profiles. In the light of this information, Nesterova et al (9) have published another article in the Journal of American Chemical Society in 2009 as a follow up study (9). In this study, authors, for the first time, have designed, prepared, and evaluated the use of double-labeled dimerization-based molecular beacons A different perspective of Pc aggregation-based system (on/off probe) has been described in another study published in the Analyst in 2010.…”
Section: Clinical and Researh Consequencesmentioning
confidence: 99%
“…Water-soluble metallophthalocyanines are one class of metal complexes that were also introduced into the design of MBs by Nesterova et al [19]. They are near-IR PLS with unique photophysical characteristics, such as (1) an intrinsic propensity to form nonfluorescent H-type dimers and (2) diminished metallophthalocyanine dimerization when the Fig.…”
Section: Metal Complexesmentioning
confidence: 99%
“…Based on the optical sensitivity of phthalocyanines, they were often applied as photodynamic therapy (PDT) agents to treat cancer or against bacteria [24][25][26][27][28][29]. Besides, zinc phthalocyanines were reported recently as optical probes either in vitro or in vivo due to the low absorbance of biosystems in the near infrared spectral window [30][31][32]. Nesterova et al studied phthalocyanine dimerizationds as near infrared fluorescence probes for in vivo and in vitro DNA/RNA detection [30].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, zinc phthalocyanines were reported recently as optical probes either in vitro or in vivo due to the low absorbance of biosystems in the near infrared spectral window [30][31][32]. Nesterova et al studied phthalocyanine dimerizationds as near infrared fluorescence probes for in vivo and in vitro DNA/RNA detection [30]. Mantareva et al reported cationic zinc phthalocyanines as advanced fluorescent contrast agents for pigmented melanoma tumors [31].…”
Section: Introductionmentioning
confidence: 99%